A Quality Improvement Initiative to Reduce "Out-of-ICU" Cardiopulmonary Arrests in a Tertiary Care Hospital in India: A 2-Year Learning Experience. Issue 1 (January 2018) - Menon, Vidya P.; Prasanna, Preetha; Edathadathil, Fabia; Balachandran, Sabarish; Moni, Merlin; Sathyapalan, Dipu; Pai, Rajesh D.; Singh, Sanjeev
Abstract : Quality Problem or Issue: To assess impact of medical emergency team (MET) in reducing "out-of-ICU" cardiopulmonary arrests and identify barriers to its optimal utilization. Initial Assessment: Frequently observed critical clinical signs and laboratory values of "out-of-ICU" crashes were used to develop Amrita Early Warning Criteria. Choice of Solution: A physician-led MET was established to respond to code MET, activated by a primary nurse. Implementation: Rates of "out-of-ICU" cardiopulmonary arrests per 1000 admissions were compared in pre-MET (2013-2014) and post-MET periods (2014-2016) along with disposition following MET and mortality. Descriptive statistics and logistic regression were used for comparative analysis. Evaluation: For continued quality improvement, a Likert agreement scale questionnaire collated the nurse's feedback on MET. 386 Code MET were recorded with an activation rate of 18.8 per 1000 inpatients for 2014-2016. Common MET triggers were desaturation (53%), seizure (10%), and syncope (9%). Seventy-one percent of activations were attended within 5 minutes, with 45% reported during nurse's night shift hours. Medical emergency team interventions resulted in 59% being shifted to ICU. In the "post-MET" period, "Cold Blue" dose reduced from 6.9 in 2013-2014 to 2.6 ( P = .0002) in 2014-2015 and 3.2 ( P = .01) in 2015-2016. Ninety-three percent of the Code Blues with prior MET calls were "delayed MET" and 28% of the Code Blues without prior MET activation were "missed MET." Nurse's feedback revealed that 46% lacked knowledge of correct MET activation process while 31% expressed a fear of reprisal for inappropriate activation. Lessons Learned: Although MET intervention was successful in significantly reducing "out-of-ICU" Code Blues, focused training of nurses is required for continued quality improvement. Abstract : Supplemental Digital Content is Available in the Text.